Decoding the metabolic dialogue in the tumor microenvironment: from immune suppression to precision cancer therapies - Ruoli Wang; Jincheng Zhuang; Qi Zhang; Wantao Wu; Xinrui Yu; Hao Zhang; Zongyi Xie (Experimental Hematology & Oncology)
Abstract The tumor microenvironment (TME) represents a metabolic battleground where immune cells and cancer cells vie for essential nutrients, ultimately influencing antitumor immunity and treatment outcomes. Recent advancements have shed light on how the metabolic reprogramming of immune cells, including macrophages, T cells, and DCs, determines their functional polarization, survival, and interactions within the TME. Factors such as hypoxia, acidosis, and nutrient deprivation drive immune cells toward immunosuppressive phenotypes, while metabolic interactions between tumors and stromal cells further entrench therapeutic resistance. This review synthesizes new insights into the metabolic checkpoints that regulate immune cell behavior, focusing on processes like glycolysis, oxidative phosphorylation (OXPHOS), lipid oxidation, and amino acid dependencies. We emphasize how metabolic enzymes (e.g., IDO1, ACLY, CPT1A) and metabolites (e.g., lactate, kynurenine) facilitate immune evasion, and we propose strategies to reverse these pathways. Innovations such as single-cell metabolomics, spatial profiling, and AI-driven drug discovery are transforming our understanding of metabolic heterogeneity and its clinical implications. Furthermore, we discuss cutting-edge therapeutic approaches—from dual-targeting metabolic inhibitors to biomaterial-based delivery systems—that aim to reprogram immune cell metabolism and enhance the effectiveness of immunotherapy. Despite the promise in preclinical studies, challenges persist in translating these findings to clinical applications, including biomarker validation, metabolic plasticity, and interpatient variability. By connecting mechanistic discoveries with translational applications, this review highlights the potential of immunometabolic targeting to overcome resistance and redefine precision oncology.